Revealing the nature of low temperature photoluminescence peaks by laser treatment in van der Waals epitaxially grown WS2 monolayers - Henini, M. (Royal Society of Chemistry, 2018)
Monolayers of transition metal dichalcogenides (TMD) are promising materials for optoelectronics devices. However, one of the challenges is to fabricate large-scale growth of high quality TMD monolayers with the desired properties in order to expand their use in potential applications. Here, we demonstrate large-scale tungsten disulfide (WS2) monolayers grown by van der Waals Epitaxy (VdWE). We show that, in addition to the large structural uniformity and homogeneity of these samples, their optical properties are very sensitive to laser irradiation. We observe a time instability in the photoluminescence (PL) emission at low temperatures in the scale of seconds to minutes. Interestingly, this change of the PL spectra with time, which is due to laser induced carrier doping, is employed to successfully distinguish the emission of two negatively charged bright excitons. Furthermore, we also detect blinking sharp bound exciton emissions which are usually attractive for single photon sources. Our findings contribute to a deeper understanding of this complex carrier dynamics induced by laser irradiation which is very important for future optoelectronic devices based on large scale TMD monolayers.